Trends of Canine Rabies Lyssavirus and Impact of the Intensified Rabies Control Program in Davao City, Philippines 2006?2017. - Lachica, Z.P
Rabies remains a public health concern in the Philippines despite the national campaign against this viral disease. For instance, in Davao City ? the largest city in the Philippines ? rabies is endemic despite the implementation of Intensified Rabies Control Program (IRCP), which is comprised of mass dog vaccination, dog castration, dog impounding, and information campaigns. In this study, we report the trends of rabies in Davao City from 2006?2017, analyze the monthly pattern of rabies incidence in the city before and after the implementation of IRCP, assess the impact of IRCP using count regression models, and provide recommendations for the strategic implementation of the programs. Our result suggests that dog impounding, precipitation, and the presence of responsibly owned dogs are significantly associated with decreasing number of reported rabies cases. Thus, we recommend that, during summer seasons, the city?s impounding efforts must be intensified. Since dog impounding is resource-demanding and may cause instability in the dog population, we suggest that the city should push for the 70% minimum vaccination coverage. Finally, implementation of other interventions such as castration and information, education, and communication (IEC) sessions must be carefully assessed as well.